A massive gauge theory à la Utiyama - Cuzinatto, R. R. (2023)
Utiyama’s method is a deductive approach of building gauge theories for semi-simple groups of local transformations, including the Abelian U(1) case, the non-Abelian SU(N) group, and the gravitational interaction. Gauge theories à la Utiyama typically predict a massless gauge potential. This work brings a mass generation mechanism and Utiyama’s method together thus giving mass to the interaction boson without breaking the gauge symmetry. Herein we devote our attention to the Abelian case. Two gauge potentials are introduced: a vetor field A μ and a scalar field B. The associated gauge-invariant field strengths F μ ν and G μ are built from Utiyama’s technique. Gauge invariance requirement upon the total Lagrangian (including matter fields and gauge fields) yields the conserved currents. Finally, we study the simplest type of Lagrangian involving the field strengths and obtain the related field equation. By imposing appropriate constraints on this particular example, Stueckelberg model is recovered.